Develop Creativity, Imagination Ability, and Understanding Of Mathematics Concepts Using Geogebra As A Virtual Learning Media By Guidebooks - Nursanti, Yuli Bangun; Nurhasanah, Farida (Journal of Mathematics and Mathematics Education, 2023)
The progress of technology necessitates educators to enhance the quality of education and establish an effective and innovative learning environment. Mathematics is often a challenging field of study for students, as they struggle to comprehend abstract mathematical concepts. As professional educators, teachers must be capable of addressing these difficulties. One approach to overcoming these challenges is by providing simple and engaging learning resources for students. Technology is expected to provide convenience for teachers in improving their teaching abilities. By utilizing Geogebra, both teachers and students can engage in visual exploration to understand abstract mathematical concepts, conduct simulations, and approach problem-solving from various angles in a more intuitive manner. For instance, students can explore the relationship between a linear function and its graph by adjusting the line's parameters. The research was conducted on students in the fourth semester of mathematics education who took the Mathematics Learning Media subject, semester IV of the 2021 curriculum of the Faculty of Teacher Training and Education, the Mathematics Education Study Program at Sebelas Maret University Surakarta for the 2022/2023 academic year which consist of 44 students. Based on the conducted research, it was determined that the Geogebra application can enhance and foster the development of students' mathematical skills. Furthermore, through the visualization of guidebooks, researchers observed that students became more practical, imaginative, and inventive in explaining the implementation of the Geogebra application, particularly in the context of mathematics.